Advanced materials for renewable energy : selected peer-reviewed papers from the Annual International Conference on Renewable Energy (ICORE 2019), August 9-10, 2019, Malang, East Java, Indonesia - Aripriharta, Aripriharta; Puspitasari, Poppy (Trans Tech Publications Ltd, 2020)
The annual International Conference on Renewable Energy (ICORE 2019) was held in Malang, East Java, Indonesia on August 9 - 10, 2019. This conference is hosted by Universitas Negeri Malang, Indonesia in collaboration with the Centre of Advanced Materials for Renewable Energy (CAMRY). This volume contains papers which were presented at the annual International Conference on Renewable Energy (ICORE 2019, Indonesia, August 9 - 10, 2019) and reflect the results of research and engineering design in the area of modern materials and materials processing technologies for the various branches of modern industrial production. Functional Materials, Nanopractiles, Electrode Materials, Supercapacitors, Solar Cells, Semiconductors, Nanofluid, Coating, Polymers, Rubber, Steel, Corrosion, Heat Treatment, Electrical Discharge Machining, Biomaterials, Knee Implant, Magnesium Alloy, Cranioplasty, Antioxidant Properties, Biomass Processing, Biofuel, Combustion, Kinetic Parameters, Pyrolysis, Catalyst, Environmental Engineering, Magnetic, Sorbent, Mercury Removal, Heavy Metals, Waster Conversion Materials Science, Mechanical Engineering, Bioscience and Medicine.
Keywords: Renewable energy sources -- Congresses.; Renewable energy sources -- Environmental aspects -- Congresses.; Energy development -- Congresses.; elektronické knihy; electronic books